2020
DOI: 10.1002/ehf2.12754
|View full text |Cite
|
Sign up to set email alerts
|

The ventilatory abnormalities and prognostic values of H2FPEF score in dyspnoeic patients with preserved left ventricle systolic function

Abstract: Aims Heart failure with preserved ejection fraction (HFpEF) is one of the major diagnoses in dyspnoeic subjects, and H 2 FPEF score enables robust differentiation of HFpEF. Given ventilatory abnormalities prevail in subjects with HFpEF, the associations between H 2 FPEF score and pulmonary function remain to be elucidated. Methods and results Subjects who presented with exertional dyspnoea and had left ventricular ejection fraction of >50% were eligible for this study. Total lung capacity, forced expiratory vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The INHALER registry is a longitudinal, hospital-based cohort study of 8963 ambulatory outpatients, who complained of exertional dyspnoea and underwent cardiopulmonary examinations from August 2005 to December 2012. 15,16 All the participants are required to complete echocardiography, pulmonary function test and blood test within a month. Estimated glomerular filtration (eGFR) rate was calculated by the Chinese Modification of Diet in Renal Disease equation.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The INHALER registry is a longitudinal, hospital-based cohort study of 8963 ambulatory outpatients, who complained of exertional dyspnoea and underwent cardiopulmonary examinations from August 2005 to December 2012. 15,16 All the participants are required to complete echocardiography, pulmonary function test and blood test within a month. Estimated glomerular filtration (eGFR) rate was calculated by the Chinese Modification of Diet in Renal Disease equation.…”
Section: Study Populationmentioning
confidence: 99%
“…Although the gold standard to assess left ventricular diastolic dysfunction is the invasive hemodynamic survey to disclose abnormal left ventricular filling pressure, echocardiographic indices, including LA dilatation, decreased tissue velocity, elevated PASP and E/e′, have been recommended as indicators of diastolic dysfunction. 15,33 While restrictive spirometry pattern has been highly prevalent in heart failure patients with either preserved or reduced LVEF, 16,34 the Jackson Heart Study has revealed the association between FVC and LA volume or PASP. 9 Cuttica et al also reported that decreased FVC positively correlated with LA dimension and left ventricular mass in CARDIA study of 3000 middle-aged subjects.…”
Section: Left Ventricular Diastolic Dysfunction and Functional Vital ...mentioning
confidence: 99%